Andrographis paniculata Burm. F. in-silico analysis compounds that function as an insulin sensitizer therapy for type 2 diabetes via peroxisome proliferator activated gamma receptors (pparγ) receptor activator - Pristiyantoro, Pristiyantoro; Siswandono, Siswandono; Mumpuni, Esti (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Type 2 diabetes mellitus (T2DM), characterized by insulin resistance, requires safer PPARγ-targeting therapies to overcome the limitations of current thiazolidinediones (e.g., hepatotoxicity of pioglitazone). Andrographis paniculata, a traditional medicinal plant, contains bioactive flavonoids with putative insulin-sensitizing effects, although their PPARγ binding mechanisms remain unexplored. This study conducted in silico screening of eight A. paniculata compounds against PPARγ (PDB:5Y2O) using: (1) molecular docking (Molegro Virtual Docker 2013.6.0.0) to calculate binding affinities (MolDock/Rerank scores) and hydrogen bond interactions; (2) physicochemical profiling (ChemDraw Ultra 22.2/Chem3D Ultra 22.2) for drug-likeness parameters; and (3) ADMET prediction (pkCSM) for pharmacokinetic and toxicity assessment, with pioglitazone as the positive control. The results showed that 5,4'-dihydroxy-7,8,2',3'-tetramethoxyflavone exhibited near-native binding (MolDock: -111.653 vs pioglitazone -137.994) with optimal ligand-receptor stabilization through strong hydrogen bonds (-7.840 kcal/mol) with Ser289, His323, and Tyr473, as well as hydrophobic interactions with Phe282 and Leu330. This compound also demonstrated better aqueous solubility (-3.404 vs -4.309 log mol/L; p<0.05) and a favorable safety profile (non-hepatotoxic, AMES-negative) despite lower Caco-2 permeability (0.141×10⁻⁶ cm/s). This study identifies 5,4'-dihydroxy-7,8,2',3'-tetramethoxyflavone as a lead PPARγ agonist from A. paniculata with enhanced safety and drug-like properties. The HBond score of -7.840 suggests improved target specificity compared to pioglitazone. In vitro validation of glucose uptake modulation is recommended to confirm its therapeutic potential.